2022
DOI: 10.2196/40082
|View full text |Cite
|
Sign up to set email alerts
|

The Agreement Between Virtual Patient and Unannounced Standardized Patient Assessments in Evaluating Primary Health Care Quality: Multicenter, Cross-sectional Pilot Study in 7 Provinces of China

Abstract: Background The unannounced standardized patient (USP) is the gold standard for primary health care (PHC) quality assessment but has many restrictions associated with high human and resource costs. Virtual patient (VP) is a valid, low-cost software option for simulating clinical scenarios and is widely used in medical education. It is unclear whether VP can be used to assess the quality of PHC. Objective This study aimed to examine the agreement between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, not all investigators have found substantial benefits with the use of virtual case scenarios [20]. It was conducted a multicentric pilot study assessing the agreement between standardized patient and virtual patient assessments for evaluating primary health care quality [21]. The agreement between the two evaluation methods was low with the virtual patient results being affected by the design, usability and case conditions [21].…”
Section: Overall Judgmentmentioning
confidence: 99%
“…However, not all investigators have found substantial benefits with the use of virtual case scenarios [20]. It was conducted a multicentric pilot study assessing the agreement between standardized patient and virtual patient assessments for evaluating primary health care quality [21]. The agreement between the two evaluation methods was low with the virtual patient results being affected by the design, usability and case conditions [21].…”
Section: Overall Judgmentmentioning
confidence: 99%
“…The investigators found that working with VPs seemed to preferentially enhance students’ skills for interviewing and delivering treatment. By contrast, the student’s success working with human SPs correlated more closely with the student’s basic fund of knowledge in science and clinical areas, as it might be called upon for taking Steps 1 and 2, respectively, of the United States Medical Licensing Examination (USMLE) [ 40 ]. In short, these results suggested that a human performance system (HPS) called for a greater draw of basic and clinical facts, while VPs might be better suited to practicing bedside communication skills.…”
Section: Reviewmentioning
confidence: 99%
“…Our team also used OSPs and student standardized patients (SSPs) in early-stage teaching, which yielded positive student learning outcomes [ 8 , 9 ]. However, OSPs and SSPs require costly personnel and material resources, significantly limiting their promotion, whereas VSPs are a low-cost tool [ 21 ]. The Chengdu University of Traditional Chinese Medicine (CDUTCM) is one of the few TCM universities that launched the VSP-TCM project.…”
Section: Introductionmentioning
confidence: 99%